Upper Fourth at Malory Towers - Blyton, Enid (Egmont UK Ltd, 2015)
For 'starters', there's twin trouble with Connie and Ruth. The main pain is Gwen. To finish, there's a picnic and a midnight feast in a thunderstorm.
Keywords: Juvenile Fiction / Adventure